STL’UL NUP: LEGAL LANDSCAPES OF THE HUL’QUMI’NUM MUSTIMUHW - Morales, Sarah (Windsor Yearbook of Access to Justice, 2017)
Landscape is a part of every individual’s sense of being. However, one cannot deny the special relationships that Indigenous peoples maintain with places they have inhabited since the beginning of creation. These places are deeply imbued with meaning, and are sites of personal and community identity. In addition, these places are legal in nature. They teach Indigenous people about their legal obligations – to each other, their ancestors and the natural world. This paper examines the connection between land and law for the Hul’qumi’num Mustimuhw, a group of Island Hul’qumi’num speaking First Nations, located on southeastern Vancouver Island. It discusses how lands within Indigenous territories can be transformed into legal landscapes, when considered in relation to place, time and experience. It also examines specific legal landscapes within the Hul’qumi’num territory and explores the laws and regulations that reside within and flow from them. Through this paper, one can gain insight into how these places inform the Hul’qumi’num lgal tradition and impart important teachings to the Hul’qumi’num Mustimuhw about the nature of their relationship and their obligations to particular places and inhabitants of those places. Le paysage fait intrinsèquement partie de l’identité de chacun. Cependant, nul ne saurait nier les liens spéciaux que les peuples autochtones ont noués avec les endroits qu’ils habitent depuis le début de la création. Ces endroits revêtent un sens tout particulier pour eux et sont des lieux auxquels ils s’identifient, tant sur le plan personnel que sur le plan communautaire. De plus, ces endroits ont acquis une grande signification juridique. Ils enseignent aux Autochtones en quoi consistent leurs obligations juridiques envers eux-mêmes, envers leurs ancêtres et envers la nature. Dans ce texte, l’auteur se penche sur la relation qui existe entre le territoire et la loi pour les Hul’qumi’num Mustimuhw, groupe de Premières nations de langue «mustimuhw Hul’qumi’num» qui vit dans le sud-est de l’île de ...